2018
DOI: 10.1542/peds.2018-0331
|View full text |Cite
|
Sign up to set email alerts
|

Guideline Adoption for Community-Acquired Pneumonia in the Outpatient Setting

Abstract: Community-acquired pneumonia (CAP) is diagnosed in >1.2 million children in outpatient settings and emergency departments (EDs) each year in the United States. 1, 2 Most antibiotic prescribing for CAP occurs in the outpatient setting. In 2011, members of the Pediatric Infectious Diseases Society and Infectious Diseases Society of America published an evidence-based guideline for the management of CAP in children. The authors of the recommendations encourage prescribing narrow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In general, adherence to the medical guidelines has varied substantially and the best way to implement scientific evidence in clinical practice is still unclear. Local education programmes often increase adherence to guidelines, 8 but previous studies have reported controversial results on the impact of pneumonia guidelines 18‐20,22 . Many factors, in addition to clinical signs and symptoms, can lead to chest imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, adherence to the medical guidelines has varied substantially and the best way to implement scientific evidence in clinical practice is still unclear. Local education programmes often increase adherence to guidelines, 8 but previous studies have reported controversial results on the impact of pneumonia guidelines 18‐20,22 . Many factors, in addition to clinical signs and symptoms, can lead to chest imaging.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed an association between taking more images and prescribing more antibiotics, 5 while another found that more images resulted in fewer antibiotics 17 . Only a few studies have specifically evaluated whether clinicians followed recommendations not to take chest radiographs if they suspected the child had pneumonia 18‐20 . It has already been demonstrated that the Finnish 2014 guidelines for LRTIs in children decreased the use of racemic adrenaline in bronchiolitis 21 …”
Section: Introductionmentioning
confidence: 99%
“…23-25 Determining appropriate antibiotic use for outpatient PNA remains challenging for several reasons, including difficulties distinguishing viral from bacterial etiologies, and that recent data suggests Mycoplasma may underlie more cases than Streptococcus pneumoniae across pediatric age groups. 12,26-28…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Determining appropriate antibiotic use for outpatient PNA remains challenging for several reasons, including difficulties distinguishing viral from bacterial etiologies, and that recent data suggests Mycoplasma may underlie more cases than Streptococcus pneumoniae across pediatric age groups. 12,[26][27][28] This study is among the first to report pediatric management practices specifically from private UCCs. 29 Outpatient health care outside of the traditional settings of medical offices and EDs-specifically in retails clinics and UCC in what is often called convenience care-is a rapidly expanding market, that had a 1725% increase in claims lines between 2007 and 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, guidelines for the management of childhood CAP were published in Europe and the USA [5,6], recommending against routine use of CXR in most children in the outpatient setting, and restricting the use of CXR to children with moderate to severe signs and symptoms of CAP at risk of developing complications. Some studies have evaluated the impact of the CAP guidelines on diagnosis and treatment of childhood CAP, and did not find significant changes in CXR performance rates [11][12][13][14]. However, their study populations were limited to children with a confirmed diagnosis of CAP rather than those with signs and symptoms of a lower RTI, and they did not evaluate the impact of CXR results on antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%